2014
DOI: 10.1039/c4cp03403a
|View full text |Cite
|
Sign up to set email alerts
|

XLPE based Al2O3–clay binary and ternary hybrid nanocomposites: self-assembly of nanoscale hybrid fillers, polymer chain confinement and transport characteristics

Abstract: Transport properties of hybrid nanoparticle based cross-linked polyethylene (XLPE)-Al2O3-clay binary and ternary nanocomposites have been investigated with special significance to the hybrid effect and synergism of hybrid nanofillers. Compiling the temperature and filler effects demonstrates the self-assembly of hybrid nanofillers in confining the polymer chain dynamics. Studies on transport mechanisms, transport coefficients, and swelling parameters confirm the superior solvent resistant properties of hybrid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

7
2

Authors

Journals

citations
Cited by 44 publications
(26 citation statements)
references
References 44 publications
(36 reference statements)
1
25
0
Order By: Relevance
“…The values obtained by the fitting the above equation is furnished in Table 4. The values obtained after the fitting of the Peppas-Sahlin model is quite matching with the literatures [9,39]. From Table 4, it is clear that the the k 1 and k 2 values changes with the change blend composition.…”
Section: Theoretical Modeling Of Diffusion Behaviorsupporting
confidence: 85%
“…The values obtained by the fitting the above equation is furnished in Table 4. The values obtained after the fitting of the Peppas-Sahlin model is quite matching with the literatures [9,39]. From Table 4, it is clear that the the k 1 and k 2 values changes with the change blend composition.…”
Section: Theoretical Modeling Of Diffusion Behaviorsupporting
confidence: 85%
“…The reduction in tan delta value with the addition of nanofiller is because of the decrease in the quantity of mobile polymer chains. The amount of polymer chains immobilized because of filler addition can be determined from the volume of constrained region, C .…”
Section: Resultsmentioning
confidence: 99%
“…Effect of the blend ratio on the transport and dynamic mechanical properties of styrenebutadiene rubber (SBR)/NR blend was investigated at different temperatures by George et al 8 In recent times, in our laboratory transport properties of hybrid nanoparticle-based, crosslinked polyethylene XLPE/Al 2 O 3 -clay binary and ternary nanocomposites were reported by Jose and Thomas. 9 They investigate the transport process follows first-order kinetics and the rate constant values confirm the superior solvent resistant characteristics of nanocomposites. Last few years, several studies were reported in solvent transport characteristics of polymer nanocomposites.…”
Section: Introductionmentioning
confidence: 92%